Design of a Lockable Spherical Joint for a Reconfigurable 3-URU Parallel Platform - Matteo Palpacelli; Luca Carbonari; Giacomo Palmieri; Massimo Callegari (Robotics, 2018)
This article deals with the functional and preliminary design of a reconfigurable joint for robotic applications. Such mechanism is a key element for a class of lower mobility parallel manipulators, allowing a local reconfiguration of the kinematic chain that enables a change in platform’s mobility. The mechanism can be integrated in the kinematic structure of a 3-URU manipulator, which shall accordingly gain the ability to change mobility from pure translation to pure rotation. As a matter of fact, special kinematics conditions must be met for the accomplishment of this task. Such peculiar requirements are described and properly exploited for the design of an effective reconfigurable mechanism. A detailed description of the joint operational principle is provided, also showing how to design it when is physically located at the fixed base of the manipulator.